Nucleophilic neutral Diborane(4) compounds with sp3-sp3-hybridized Boron atoms - Himmel, Hans-Jörg (European journal of inorganic chemistry, 2018)
Borylation reactions with diborane(4) compounds are of key importance in modern synthetic chemistry. Generally, sp2-sp2-hybridized diborane(4) compounds are used for this purpose; these can be regarded as boryl-substituted boranes and consequently react as electrophiles. In contrast, the chemistry of nucleophilic, electron-rich sp3-sp3-hybridized diborane(4) compounds is a very underdeveloped research field. This review highlights some aspects of this chemistry, showing that it offers great new opportunities for diboration and boron-boron coupling reactions. The discussion focusses primarily on especially nucleophilic doubly guanidinate-bridged diborane(4) compounds.
First published: 07 Febrary 2018
Gesehen am 15.01.2020
sp3: Zahl 3 ist hochgestellt